INTERNSHIP REMUNERATION FOR STUDENTS UNDER INDONESIAN LAW - Aafiyah Salsabila Ramadhan; Andi Azraf Akbar Rezal; Febri Rahmatullah; Komang Ratih Radityari (Problematika Hukum, 2021)
Work experience is an essential part of gaining the experience and skills needed for post-graduate employment. They provide students with valuable work experience, access to professional networking, and the opportunity to explore different career opportunities. They open themselves and their minds to gain new knowledge and adapt to a new environment. Only if the company does and appreciates all their hard work, this is certainly a positive value. However, companies in Indonesia rarely appreciate the hard work during internship by giving them either low remuneration or no remuneration at all. There are a number of regulations under Indonesian law that explain the rights and responsibilities of interns, that is, they have rights that are protected by the state, which includes the right to compensation. Several questions arise when this issue is raised. What are Indonesian regulations regarding rights and obligations of interns and companies? What is international best practice regarding placements? In order to avoid underpayment of interns, what is the way forward for Indonesia in this area?Keywords: Keywords: Remuneration, Students, Indonesian Law